Potensi Senyawa Bioaktiv Spon Laut Axinella Carteri Asal Sumatera Barat - Handayani, Dian (Fakultas Farmasi Universitas Andalas, 2012)
This paper reports the bioactivity potency of the marine sponge Axinella carteri, which has been investigated for its anticancer, antibacterial, antifungal and antiviral activities. This sponge is one of the most abudance organism in the coastline of West Sumatera.